MENINGKATKAN KREATIVITAS SISWA DENGAN MEMANFAATKAN LIMBAH TUTUP BOTOL SEBAGAI TEMPAT TISU - Baiq Rizki Hidayati; Assura Badia; Khairunnisa Asmiarni; Muhammad Hamdani; Nia Bidayati Sholehah; Rina Apriliana (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The training activity of making tissue holders from used bottle caps aims to foster creativity, skills, and environmental awareness in elementary school students. The training was conducted by students in grades 6A and 6B, each divided into two groups. The implementation method was carried out through the stages of collecting materials, explaining the concept of recycling, practical production, and evaluation of the work. The results of the activity showed that students were able to produce creative works that are useful and highly aesthetic. Furthermore, this activity fostered a spirit of cooperation, responsibility, and awareness of the importance of managing plastic waste